The Translator as 'Language Planner': Syntactic Calquing in an English-Spanish Technical Translation of Chemical Engineering - Montero-Martinez, Silvia; Fuertes-Olivera, Pedro; García de Quesada, Mercedes (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2001)
AbstractThis article focuses on technical translation and the demands imposed on subject-field expert translators who must decide how they can reconcile the linguistic constraints imposed by a particular language with the communicative expectations found in a particular domain. Our main hypothesis is that experts typically resort to syntactic calquing to render phraseological units such as lexical collocations. By so doing they reinforce their role as language planners not only by introducing terminology into the TL but also by imposing SL norms within the expert community. Hence, the role of translation during the process of term documentation should be enhanced.